A trivalent chromium electroplating solution
By using the combination of the chromium chromium plating solution and the combination of auxiliary collaterals and the multi -arm polyethylene glycol as a dispersant, the problem of slow and high hardness of the sedimentary rate of tritinal chromium plating liquid plating liquid is solved. A higher sedimentary rate and higher coating hardness.
Patent Information
- Application Number
- CN202211583858.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-10
AI Technical Summary
The trivalent chromium plating solution has the problem of slow deposition rate of the coating and insufficient fine grains, resulting in low hardness.
The combination of anemia and auxiliary complexing agent N-hydroxyettethalmia titanine, ethylene glycol (2-aminobeyl ether) tethalotic acid and amino glycosate is combined with multi-arm polyethylene glycol as Differentians, regulate the cooperation and decentralization effect of the collaboration to improve the deposition rate and hardness of chromium plating.
While maintaining a higher sedimentary rate, we can obtain more fine grains and higher coating hardness, and solve the problem of low hardness of trice chromium plating fluid.
Smart Images

Figure GDA0005034678920000031
Abstract
Description
Technical Field
[0001] The present application relates to the field of electroplating technology, and in particular, to a trivalent chromium electroplating solution. Background Art
[0002] Chromium plating has good hardness and corrosion resistance. Hexavalent chromium is highly toxic, and trivalent chromium is much more environmentally friendly than hexavalent chromium. Hexavalent chromium plating solution is gradually being replaced by trivalent chromium plating solution. However, trivalent chromium plating solution also has the problem of slow deposition rate of the coating and insufficient grain size, resulting in low hardness. Summary of the invention
[0003] In order to solve the above technical problems, the inventors have conducted a large number of experiments and studies and found that one of the main reasons affecting the slow deposition rate of trivalent chromium plating is the complexing agent. At the same time, by using some special dispersants, relatively fine grains can be obtained while maintaining a higher deposition rate. For this purpose, the present application provides a trivalent chromium electroplating solution.
[0004] This application adopts the following technical solutions:
[0005] A trivalent chromium electroplating solution comprises the following raw material components: 15-60 g / L of main salt, 25-50 g / L of main complexing agent, 0.5-10 g / L of auxiliary complexing agent, 130-200 g / L of conductive salt, 0.05-0.2 g / L of reducing agent, 0.01-0.1 g / L of dispersant and 30-120 g / L of buffer;
[0006] The auxiliary complexing agent is selected from one or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosic acid.
[0007] Preferably, the main salt is selected from one or more of chromium sulfate and its hydrate, potassium chromium sulfate and its hydrate and basic chromium sulfate.
[0008] Preferably, the main complexing agent is selected from one or more of tartaric acid, citric acid, adipic acid and its salts, succinic acid and its salts, glycolic acid, oxalic acid and its salts, malic acid, formic acid and acetic acid.
[0009] Preferably, the auxiliary complexing agent is composed of two or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and glucosamine.
[0010] Preferably, the weight of the main complexing agent is 10-50 times the weight of the auxiliary complexing agent.
[0011] Preferably, the conductive salt is selected from one or more of potassium sulfate, sodium sulfate, potassium chloride, sodium chloride, ammonium sulfate and potassium aluminum sulfate.
[0012] Preferably, the reducing agent is selected from one or more of sodium bisulfate, glucosamine, vitamin C, ascorbic acid and its salts, hydrazine hydrate, carotenoids and isoascorbic acid and its salts.
[0013] Preferably, the dispersant is selected from one or more of polyethylene glycol and multi-arm polyethylene glycol.
[0014] More preferably, the average relative molecular weight of the polyethylene glycol and multi-arm polyethylene glycol is no more than 5,000.
[0015] Preferably, the buffer is selected from one or more of boric acid, sodium citrate, phthalic acid and its salts, aluminum sulfate and aminoacetic acid.
[0016] In summary, this application has the following beneficial effects:
[0017] 1. The trivalent chromium electroplating solution of the present application adopts a conventional main complexing agent, combined with auxiliary complexing agents N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and glucosamine, which have a good complexing effect on trivalent chromium, reduce the complexing effect of water and the concentration of free trivalent chromium ions, on the one hand, can relatively stably complex trivalent chromium ions, on the other hand, avoid too strong complexing, which will lead to a slow rate of conversion of trivalent chromium into metallic chromium, affecting the deposition rate of chromium; 2. The trivalent chromium electroplating solution of the present application adopts polyethylene glycol and multi-arm polyethylene glycol as dispersants, which can not only play a good dispersing effect, but also the inventors have found that the multi-arm polyethylene glycol has a better dispersing effect, which can make the crystallization of the chrome plating layer denser and the hardness higher. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below.
[0019] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0020] The present application proposes a trivalent chromium electroplating solution, comprising the following raw material components, 15-60 g / L of main salt, 25-50 g / L of main complexing agent, 0.5-10 g / L of auxiliary complexing agent, 130-200 g / L of conductive salt, 0.05-0.2 g / L of reducing agent, 0.01-0.1 g / L of dispersant and 30-120 g / L of buffer;
[0021] The auxiliary complexing agent is selected from one or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosic acid.
[0022] Furthermore, the trivalent chromium electroplating solution includes the following raw material components: 18-50 g / L main salt, 30-50 g / L main complexing agent, 1-7 g / L auxiliary complexing agent, 140-180 g / L conductive salt, 0.1-0.2 g / L reducing agent, 0.03-0.1 g / L dispersant and 50-100 g / L buffer.
[0023] In the present application, further, the main salt is selected from one or more of chromium sulfate and its hydrate, potassium chromium sulfate and its hydrate and basic chromium sulfate. In addition to hexahydrate, the hydrate of chromium sulfate also has a variety of compounds containing different crystal water. Potassium chromium sulfate hydrate can be potassium chromium sulfate dodecahydrate.
[0024] In the present application, further, the main complexing agent is selected from one or more of tartaric acid, citric acid, adipic acid and its salts, succinic acid and its salts, glycolic acid, oxalic acid and its salts, malic acid, formic acid and acetic acid. Further, the main complexing agent is selected from one or more combinations of tartaric acid, citric acid, and malic acid.
[0025] In the present application, further, the auxiliary complexing agent is composed of two or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and glucosamine acid. The inventors found that the auxiliary complexing agent is composed of two or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and glucosamine acid. Compared with a single auxiliary complexing agent, the rate of chromium deposition is faster. In the present application, when the auxiliary complexing agent is composed of two, the weight ratio of the two auxiliary complexing agents can be 5:1-1:5; when the auxiliary complexing agent is composed of three, the weight ratio of the three auxiliary complexing agents can be 1-10:1-10:1-10.
[0026] In the present application, further, the weight of the main complexing agent is 10-50 times the weight of the auxiliary complexing agent. The inventors found that the chromium deposition effect is better when the weight ratio of the main complexing agent to the auxiliary complexing agent is within a certain range.
[0027] In the present application, further, the conductive salt is selected from one or more of potassium sulfate, sodium sulfate, potassium chloride, sodium chloride, ammonium sulfate and potassium aluminum sulfate. Further, the conductive salt is selected from one or more of potassium sulfate, sodium sulfate, ammonium sulfate and potassium aluminum sulfate.
[0028] In the present application, the function of the reducing agent is to reduce or prevent trivalent chromium from being oxidized to hexavalent chromium. Further, the reducing agent is selected from one or more of sodium bisulfate, glucosamine, vitamin C, ascorbic acid and its salts, hydrazine hydrate, carotenoids and isoascorbic acid and its salts.
[0029] In the present application, further, the dispersant is selected from one or more of polyethylene glycol and multi-arm polyethylene glycol. Further, the dispersant is multi-arm polyethylene glycol.
[0030] Multi-arm polyethylene glycol refers to a molecular structure containing multiple polyethylene glycol segments. According to the different cores, it can be divided into three-arm, four-arm, six-arm, eight-arm, ten-arm, etc. For example, the structure of a six-arm polyethylene glycol is shown in the following formula (1):
[0031]
[0032] Furthermore, the average relative molecular weight of polyethylene glycol does not exceed 1200; further, the average relative molecular weight of multi-arm polyethylene glycol does not exceed 3000. The average relative molecular weight of polyethylene glycol and multi-arm polyethylene glycol is relatively low, and the higher the activity of polyethylene glycol and multi-arm polyethylene glycol, the better the dispersion effect.
[0033] In the present application, further, the buffer is selected from one or more of boric acid, sodium citrate, phthalic acid and its salts, aluminum sulfate and aminoacetic acid.
[0034] The trivalent chromium electroplating solution of the present application can be prepared as follows: prepare the weight of each raw material component, add the main salt, the main complexing agent and the auxiliary complexing agent into water, stir and dissolve, then heat to 65±5°C and keep warm for 2±0.5 hours, add the dispersant, the reducing agent, the conductive salt and the buffer, stir and dissolve.
[0035] When the trivalent chromium electroplating solution of the present application is used, the temperature of the electroplating solution is controlled at 40±5°C, and the current density is controlled at 15-40A / dm 2 , the electroplating time is 1 hour to 2 hours, and a coating thickness of about 50-120 μm can be obtained. During the electroplating process, the pH of the electroplating solution is controlled at 2-4, which can be adjusted with a sulfuric acid solution or a sodium hydroxide solution. In this application, the current density can be gradually increased in the initial stage, that is, the time from 0 to the specified current density is 30s-120s, which helps to improve the bonding strength between the chromium plating layer and the substrate.
[0036] The trivalent chromium electroplating solution of the present application will be described in detail below in combination with embodiments, comparative examples and experimental data.
[0037] Example 1
[0038] According to the concentration of raw material components, 38g / L chromium sulfate hexahydrate, 35g / L malic acid, 3g / L N-hydroxyethylethylenediaminetriacetic acid, 150g / L sodium sulfate, 0.15g / L ascorbic acid, 0.05g / L polyethylene glycol-400 (400 represents the molecular weight) and 70g / L boric acid, add chromium sulfate hexahydrate, malic acid and N-hydroxyethylethylenediaminetriacetic acid into water, stir to dissolve, then heat to 65±2°C and keep warm for 2 hours, add polyethylene glycol-400, ascorbic acid, sodium sulfate and boric acid, stir to dissolve, and adjust the pH to 2.5-3.
[0039] Example 2
[0040] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was replaced by an equal weight of ethylene glycol bis(2-aminoethyl ether)tetraacetic acid, and the remaining steps remained unchanged.
[0041] Example 3
[0042] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was replaced by an equal weight of glucosamine acid, and the other steps remained unchanged.
[0043] Example 4
[0044] In Example 1, N-hydroxyethylethylenediaminetriacetic acid is replaced by an equal weight combination of N-hydroxyethylethylenediaminetriacetic acid and aminoglucosic acid in a weight ratio of 1:2, and the other steps remain unchanged.
[0045] Example 5
[0046] In Example 1, N-hydroxyethylethylenediaminetriacetic acid is replaced by an equal weight of a combination of ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosic acid in a weight ratio of 1:1, and the other steps remain unchanged.
[0047] Example 6
[0048] In Example 1, polyethylene glycol-400 was replaced by an equal weight of six-arm polyethylene glycol (molecular weight 2000, purchased from Guangzhou Carbon Water Technology Co., Ltd.), and the other steps remained unchanged.
[0049] Example 7
[0050] According to the concentration of raw material components, 40g / L chromium sulfate hexahydrate, 42g / L tartaric acid, 2g / L ethylene glycol bis(2-aminoethyl ether) tetraacetic acid, 150g / L sodium sulfate, 0.16g / L isoascorbic acid, 0.07g / L six-arm polyethylene glycol (molecular weight 2000, purchased from Guangzhou Carbon Water Technology Co., Ltd.) and 65g / L boric acid, add chromium sulfate hexahydrate, tartaric acid and ethylene glycol bis(2-aminoethyl ether) tetraacetic acid to water, stir to dissolve, then heat to 65±2°C and keep warm for 2 hours, add six-arm polyethylene glycol, isoascorbic acid, sodium sulfate and boric acid, stir to dissolve, and adjust the pH to 2.5-3.
[0051] Example 8
[0052] In Example 7, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid was replaced by an equal weight of a combination of N-hydroxyethylethylenediaminetriacetic acid and aminoglucosic acid in a weight ratio of 3:2, and the other steps remained unchanged.
[0053] Example 9
[0054] In Example 7, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid was replaced by an equal weight of a combination of ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosic acid in a weight ratio of 2:3, and the other steps remained unchanged.
[0055] Example 10
[0056] In Example 7, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid was replaced by an equal weight of a combination of N-hydroxyethylethylenediaminetriacetic acid and aminoglucosic acid in a weight ratio of 1:1, and the other steps remained unchanged.
[0057] Embodiment 11
[0058] In Example 7, the six-arm polyethylene glycol was adjusted from 0.07 g / L to 0.09 g / L, and the other steps remained unchanged.
[0059] Comparative Example 1
[0060] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was not added, and the remaining steps remained unchanged.
[0061] Comparative Example 2
[0062] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was replaced by an equal weight of EDTA, and the remaining steps remained unchanged.
[0063] Comparative Example 3
[0064] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was replaced by 0.5 g / L EDTA, and the other steps remained unchanged.
[0065] Comparative Example 4
[0066] In Example 1, N-hydroxyethylethylenediaminetriacetic acid was replaced by an equal weight of aspartic acid, and the remaining steps remained unchanged.
[0067] Comparative Example 5
[0068] In Example 7, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid was replaced by an equal weight of EDTA, and the remaining steps remained unchanged.
[0069] Comparative Example 6
[0070] In Example 7, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid was replaced by an equal weight of aspartic acid, and the remaining steps remained unchanged.
[0071] application
[0072] After cleaning the bright nickel plated workpiece, electroplating was performed using the trivalent chromium electroplating solution of Examples 1-11 and Comparative Examples 1-6. The temperature of the electroplating solution was controlled at 40±2°C, and the current density was controlled at 20A / dm 2 The electroplating time is 60 minutes. The pH of the electroplating solution is controlled at 2.5-3.5 during the electroplating process. In the initial stage of electroplating, the current density is gradually increased from 0 to 20A / dm 2 The time is 80s.
[0073] Coating thickness test: Use XRF coating thickness gauge to test.
[0074] Coating hardness test: Tested using a micro Vickers hardness tester.
[0075] The results are shown in Table 1.
[0076] Table 1
[0077] Thickness(μm) Hardness (HV) Example 1 67 850 Example 2 69 830 Example 3 63 880 Example 4 78 820 Example 5 80 840 Example 6 70 980 Example 7 73 960 Example 8 85 930 Example 9 83 950 Example 10 89 910 Embodiment 11 72 1000 Comparative Example 1 55 820 Comparative Example 2 37 860 Comparative Example 3 42 830 Comparative Example 4 58 850 Comparative Example 5 49 900 Comparative Example 6 65 910
[0078] Compare the results in Table 1. Comparing Examples 1-6 and Comparative Examples 1-4, the auxiliary complexing agent of the present application can significantly increase the deposition rate of the chromium plating layer and maintain a relatively high hardness. When the auxiliary complexing agent is a combination of two, the deposition rate of the chromium plating layer is higher. When the dispersant is multi-arm polyethylene glycol, the hardness of the obtained chromium plating layer is significantly higher, indicating that the chromium plating layer is fine and dense.
[0079] Comparative Examples 7-11 and Comparative Examples 5 and 6 have the same technical effects.
[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A trivalent chromium electroplating solution, characterized in that: The invention comprises the following raw materials: 15-60 g / L main salt, 25-50 g / L main complexing agent, 0.5-10 g / L auxiliary complexing agent, 130-200 g / L conductive salt, 0.05-0.2 g / L reducing agent, 0.01-0.1 g / L dispersant and 30-120 g / L buffering agent; The auxiliary complexing agent is selected from one or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosamine acid; The main salt is selected from one or more of chromium sulfate and its hydrate, potassium chromium sulfate and its hydrate, and basic chromium sulfate; The main complexing agent is selected from one or more of tartaric acid, citric acid, adipic acid and its salts, succinic acid and its salts, glycolic acid, oxalic acid and its salts, malic acid, formic acid and acetic acid.
2. The trivalent chromium electroplating solution according to claim 1, characterized in that: The auxiliary complexing agent is composed of two or more of N-hydroxyethylethylenediaminetriacetic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid and aminoglucosic acid.
3. The trivalent chromium electroplating solution according to claim 1, characterized in that: The weight of the main complexing agent is 10-50 times the weight of the auxiliary complexing agent.
4. The trivalent chromium electroplating solution according to claim 1, characterized in that: The conductive salt is selected from one or more of potassium sulfate, sodium sulfate, potassium chloride, sodium chloride, ammonium sulfate and potassium aluminum sulfate.
5. The trivalent chromium electroplating solution according to claim 1, characterized in that: The reducing agent is selected from one or more of sodium bisulfate, glucosamine, vitamin C, ascorbic acid and its salts, hydrazine hydrate, carotenoids and isoascorbic acid and its salts.
6. The trivalent chromium electroplating solution according to claim 1, characterized in that: The dispersant is selected from one or more of polyethylene glycol and multi-arm polyethylene glycol.
7. The trivalent chromium electroplating solution according to claim 6, characterized in that: The average relative molecular weight of the polyethylene glycol and multi-arm polyethylene glycol is no more than 5000.
8. The trivalent chromium electroplating solution according to claim 1, characterized in that: The buffer is selected from one or more of boric acid, sodium citrate, phthalic acid and its salts, aluminum sulfate and aminoacetic acid.
Citation Information
Patent Citations
Glucosaminic-acid cyanide-free gold-plating electroplating liquid and electroplating method thereof
CN105441995A
Electroplating liquid of trivalent chromium system for ferrochrome electrodeposition and preparation method thereof
CN108866586A